Análise de estratégias inovativas de consolidação de arranjo produtivo local de confecção do estado do Paraná - Kachba, Yslene Rocha (2009)
In the current scenario of mass production of fashion, the competition of the industrial manufacturing has increased in national and international markets. Moreover, in the last two decades, the competition was a result of the opening of market for the Brazilian, and the amazing potential of Asian countries to conquer new markets in this sector. That causes a certain "competitive pressure", where the challenge is to produce it with greater flexibility, quality, and innovation in a shorter time. These factors make it tricky to relate to the reality of innovation in products of clothing, as they have their life cycle limited to the maximum of six months. In this sense, this research presents an analysis from the strategic management of innovation for the consolidation of Local Productive Arrangements (LPAs) of consumer goods. The research examines the innovations presented in the strategic planning of 5 LPAs located in the State of Parana. It was considered the LPAs organized for more than 4 years from the consolidation strategies, and the roadmapping project `Strategic Routes for the Future of Parana’s Industry’ for innovation management, innovation in marketing, innovation in process, product innovation, and new materials. But there is a difficulty in transferring technology on the process of innovation chain, particularly regarding to the management culture of product development processes in conjunction and cooperation of suppliers, especially of textile, since they are characterized by the presentation of hierarchical among the companies in LPA 4 and, consequently, do not score the importance of creating partnerships with technological innovation for Micro and Small Enterprises, organized in the same network.